The first decade of service dominant logic research - a bibliometric analysis - Silva, S. V. Da; António, N.; Crespo de Carvalho, J. (International Journal of Business Excellence, 2018)
This paper provides an analysis of the first decade of research on the service-dominant logic (S-D logic) approach to marketing. It adopts a multi-step methodology the use of bibliometric techniques. 1,036 bibliographic records were initially identified. These were subject to two refinement stages, resulting in a total of 540 records which consisted of publications from 975 authors, published in 162 journals. Statistical analysis identified the most influential academic institutions, journals and articles in this particular field of research, revealing their character in terms of types of publication, its geographical distribution, and annual output. Four clusters of journals in regards to their output versus citation impact were further identified, with six journals divided in two groups emerging as the leading journals in the field of S-D logic